ChemInform Abstract: Iridium(III)‐Bis(oxazolinyl)phenyl Catalysts for Enantioselective C—H Functionalization. Issue 45 (14th October 2013) - Owens, Clayton P.; Varela‐Alvarez, Adrian; Boyarskikh, Vyacheslav; Musaev, Djamaladdin G.; Davies, Huw M. L.; Blakey, Simon B.
Abstract A series of iridium(III) phebox complexes are synthesized and screened for the enantioselective C‐H functionalization.